Helminthiasis among Indian Preschoolers from Urban Areas in Penang - Vikneswaran Sabramani,; Halim Ismail,; Asrul Abdul Wahab, (Universiti Kebangsaan Malaysia, 2015)
Introduction Helminthiasis is a common parasitic condition particularly among children in rural areas in developing countries where poor hygiene standard is practiced. The study aimed to determine the prevalence of helminthiasis among Indian preschoolers in urban areas in Penang and its associated factors. Methods A total of 194 urban Indian preschoolers aged 4 to 6 years old were selected randomly from 11 kindergartens in the state of Penang for this cross sectional study. Data collection was carried out in 2 phases. First, microscopic stool examinations were done to examine the presence of helminths. Second, self administered questionnaires which inquired about human, environment and socioeconomic factors were completed by the parents/guardians. Results The overall prevalence of helminthiasis was 7.2% and the most frequently encountered infective agent was Ascaris lumbricoides (57.1%) and followed by the tapeworms (42.86%). The logistic regression indicated that habitual thumb sucking (AOR= 5.6. 95%CI: 1.73-18.39) and families owning domestic pets (AOR= 3.2; 95%CI: 1.03-10.14) were the significant contributing factors to helminthiasis among the Indian pre-schoolers in urban Penang. Although the prevalence of helminth infection among the urban Indian preschoolers is lower than rural area, it is still a public health concern. Children habitual thumb sucking and rearing domestic pets at home were the significant contributing factors in helminthiasis. Conclusion Prevention strategy should focus on health education and promotion among adults and children, awareness on domestic animal hygiene and maintaining good environmental sanitation. Multi agency collaboration is clearly essential, especially between state health, education and veterinary departments in curbing this disease.